The study on the effect of population density on radio frequency interference (RFI) analysis on dynamic spectrum at selected CALLISTO stations - Z. N Zainud-din; N. H Sabri; R. Umar; C. Monstein (Physical Sciences and Technology, 2021)
Radio Frequency Interference (RFI) has become a critical issue in radio astronomy observation in recent years. Compact Astronomical Low-Cost Instrument for Spectroscopy in Transportable Observatories (CALLISTO) is a worldwide network of spectrometer system for solar activity monitoring. The detection of solar radio bursts is being interrupted due to RFI as these stations are held on the ground. Since RFI signals are being detected from surrounding, this gives inaccurate data for ground base station observations. RFI sources are mostly from man-made devices. This paper study analysis of RFI level at selected CALLISTO stations by using Kurtosis Analysis. Data from Banting, Malaysia, Sumedang, Indonesia, Ooty, India and Daejeon, South Korea stations for two months (45–870 MHz) that contain solar burst and no solar burst had been selected. The kurtosis value is then compared with the population density to get the relationship between the population density and the RFI level. The highest average of kurtosis value indicates the lowest of radio frequency interference at these sites. MATLAB software was used for the data analysis and Microsoft Excel for the RFI profiling graphing. The results show that the high population density is not a main factor that contributes the interference towards the surrounding.